(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The study of the peculiarities of defining the semantics of toponyms is a necessary stage in the development of regional linguistics. The question of the essence of the semantics of proper names, and even more so of such special names as toponyms, is being ambiguously resolved. Defining the semantics of a toponym, we base on the semantics of the original word (appellative), taking into account the uniqueness of the toponym, its place in the system of proper names and common names, the peculiarities of its use in the speech of individuals and entire collectives at different time slices, the attitude of speakers to the named objects, the peculiarities of the linguistic means used in toponymy, as well as the originality of each toponym separately.